Effects Of Financial Strategies on Sustainability of Agricultural-Based Non-Governmental Organizations in Nairobi, Kenya (Cuea Journal of Business and Economics, 2025)
Agriculture plays a central role in Kenya’s economy by providing livelihoods for the rural population and contributing to export earnings. However, agriculture-based NGOs face persistent financial instability, with limited donor funding allocated to the sector, threatening their sustainability. This study examined how financial strategies affect the sustainability of agriculture-focused NGOs in Nairobi County, emphasizing risk management, investment choices, financial diversification, and cost control. Guided by theories including the resource-based view, agency theory, triple bottom line, portfolio theory, and budgetary control, the research employed a descriptive survey design targeting 1,143 NGOs. In this research, 296 finance managers were surveyed using questionnaires. The study ensured the data's reliability through preliminary testing and by verifying key statistical assumptions. Using SPSS version 25 for analysis, the results demonstrated that all four financial strategies examined—risk management, financing diversification, cost control, and investments—had a significant positive impact on sustainability. The study also found that an organization's access to resources plays a key role in strengthening these connections. The central conclusion is that for long-term survival, NGOs must prioritize effective risk management, diversify their funding sources, maintain strict cost control, and make sound investments. To achieve this, the study advises organizations to develop proactive approaches to risk, create diverse income streams through local fundraising and social enterprises, and make the most of their financial and human capital.